Gene-gene interactions and prevalence of gene polymorphism associated with disorders of hemostasis and folate metabolism in patients with recurrent miscarriage - Nataly I Frolova; Tatiana E Belokrinitskaya; Nataliya N Strambovskaya; Evgeniya P Belozertseva (IP Berlin A.V., 2019)
Aim. To assess the association between polymorphisms of FVL-1691G>A, FII-20210G>A, MTHFR-677C>T, MTHFR-1298А>C, РАІ-1-6755G>4G and their combinations in patients with recurrent early pregnancy losses (RPL). Materials and methods. This study included two groups of women (age range 20-35 years): 50 currently non-pregnant women with a history of 2-5 unexplained recurrent early spontaneous abortion and unknown causes of miscarriages (RPL group), and 50 currently non-pregnant women with a history of having given birth to at least one live baby and without a history of spontaneous abortion, preterm labor, stillbirth, preeclampsia and other pregnancy complications (control group). Gene polymorphisms were detected by the technique of polymerase chain reaction-real time. We have analyzed the frequencies, Hardy-Weinberg equilibrium, V-Kramer test, χ2 test, odds ratio (OR) and its 95% confidence interval (95% CI). General (χ2 test, df=2) and multiplicative (χ2 test, df=1) models of inheritance have been used to assess the presence of gene polymorphisms. Results. Significant association between heterozygotes genotype PAI-1-5G4G (72% vs 32%, p=0.000; OR 5.46; 95% CI 2.32-12.87) and RPL was found. Heterozygous genotype FII-20210GA was detected only in RPL group (4% vs 0%). Combinations of genetic polymorphisms of FVL-1691G>A, FII-20210G>A, MTHFR-677C>T, MTHFR-1298А>C, РАІ-1-6755G>4G increase the risk of RPL by 2.4 times (56% vs 20%; χ2=29.20, р=0.000; OR 3.69, 95% CI 1.52-8.97; strong V-Kramer association). The combination of two heterozygotes variants of minor alleles was found to be a risk factor for RPL (34% vs 10%; χ2=8.73, р=0.004; OR 4.64, 95% CI 1.55-3.84). Combined PAI-1-5G4G + FVL-1691GA genotypes was detected only in RPL group of women (2% vs 0%). No significant association between the combination of three heterozygotes variants of minor alleles and RPL. Conclusion. Our data suggest significant gene-gene interaction of the heterozygotes variants of minor alleles of FVL-1691G>A, FII-20210G>A, MTHFR-677C>T, MTHFR-1298А>C, РАІ-1-6755G>4G polymorphisms in patients with recurrent miscarriage. Combined genotypes FVL-1691GA/PAI-1-5G4G can be considered as a genetic molecular predictor of recurrent early pregnancy losses.